Diffusion tensor imaging determines three‐dimensional architecture of human cervix: a cross‐sectional study. (11th December 2017) - Nott, JP; Pervolaraki, E; Benson, AP; Bonney, EA; Pickering, JD; Wilkinson, N; Simpson, NAB
Abstract : Objective: To determine the microarchitecture of the cervix using high‐resolution diffusion tensor (DT) magnetic resonance imaging (MRI). Design: Cross‐sectional study. Setting: Leeds, UK. Sample: Women undergoing hysterectomy for benign pathology. Methods: Ex‐vivo DT‐MRI measurements were obtained using a 9.4‐T Bruker nuclear magnetic resonance (NMR) spectrometer on seven fixed human cervices obtained at hysterectomy. A deterministic fibre‐tracking algorithm was used to indirectly visualise underlying fibre organisation. Inter‐regional differences in tissue structure were sought using quantitative measurements of diffusion. Main outcome measure: The identification of an occlusive structure in the region corresponding to the internal cervical os. Results: Fibre tracking demonstrated two regions: an outer circular and inner longitudinal layer. The total circumferential tract volume (TV) was greatest in the proximal region of the cervix (TV: proximal, 271 ± 198 mm 3 ; middle, 186 ± 119 mm 3 ; distal, 38 ± 36 mm 3 ). Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) measurements were significantly different between regions in all samples ( P < 0.0005), indicating greater tract density and organisation towards the internal os. Conclusion: Fibre tracking infers a system of dense, well‐defined, encircling fibres in the proximal region of the cervix, corresponding to the location of the internal os. These findings may provide evidence of specific anatomic microarchitecture within the cervix able to resist intrauterine forces associated with pregnancy. Tweetable abstract: Diffusion‐tensor MRI derived tractography identified well‐defined encircling fibres at the internal os. Tweetable abstract: Diffusion‐tensor MRI derived tractography identified well‐defined encircling fibres at the internal os.